“Not Just Being Out on the Streets”: Serving LGBTQ+ Youth Experiencing Homelessness in Milwaukee - (:unkn) unknown (My University, 2022)
LGBTQ+ youth homeless is a pressing topic for geographic study, as LGBTQ+ youth are overrepresented in youth homeless populations (Cunningham et al. 2014; Morton et al 2018). The conditions that create urban youth homelessness are social, material, and spatial. This research aims to examine service providers’ perspective of the conditions of LGBTQ+ youth homelessness in Milwaukee. Specifically, I examine how service providers in the city understand LGBTQ+ youth homelessness, where service providers identify barriers and gaps in the city for LGBTQ+ homeless youth, and ways service providers challenge and/or reproduce LGBTQ+ youth homelessness in their care work. Drawing on feminist and queer geographic literature, and informed by feminist care ethics, I conduct qualitative research with participants from four non-profit organizations across Milwaukee. From interviews with these service providers, I employ a thematic analysis of the conditions of LGBTQ+ youth homelessness in the city. In this thesis, I argue that service providers understand LGBTQ+ youth homelessness as informed by urban conditions that are reproduced through hierarchies of race, class, gender, sexuality, through the built environment, and through neoliberal logics of care.
Keywords: feminist care ethics; feminist geography; LGBTQ+ youth homelessness; queer geographies; urban geography; youth homelessness